POSTURAL MONITORING IN A CIVIL CONSTRUCTION TEAM COMPRISING CIVIL MAINTENANCE OFFICERS (Editora Impacto Científico, 2025)
The influence of ergonomics in civil construction, predominantly in roles such as maintenance officers focused on Occupational Health and Safety (OHS), specifically its practical impact on the daily routine of workers and employers after the implementation of AET. To achieve the results, a qualitative and quantitative survey will be conducted, applying the REBA (Rapid Entire Body Assessment) method for postural assessment in order to filter the data necessary to explain the topic of postural monitoring. Thus, the general objective was outlined to highlight the changes that occurred before and after the implementation of corrective measures. Among the specific objectives are to understand the changes that have occurred in practice on the factory floor and to highlight the transformations in the lives of workers in their fields of work. Safety at work is very important in the lives of workers and in the routines of industries, which are represented by employers. The set of labor laws issued in Brazil seeks to efficiently achieve the well-being of workers in industries in accordance with the labor relationship regime described in the Consolidation of Labor Laws (CLT). It is expected that the indicators will prove to be a solution for a time of countless innovations, with the emergence of artificial intelligence (AI) that is entering the most varied sectors of industry and civil construction, where employees work regular or special shifts. Among these positive results, it is expected to streamline communication between employers and regulatory agencies, as well as speed up the response of agencies to demands that directly involve workers, such as reporting workplace accidents (CAT) and leave notifications, among others.